2007
DOI: 10.1021/op700042w
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Scaleable Synthesis of 1R,5S-Bicyclo[3.1.0]hexan-2-one:  The Development of a Catalytic Lithium 2,2,6,6-Tetramethylpiperidide (LTMP) Mediated Intramolecular Cyclopropanation of (R)-1,2-Epoxyhex-5-ene

Abstract: An efficient synthesis of 1R,5S-bicyclo[3.1.0]hexan-2-one from (R)-1,2-epoxyhex-5-ene is described. Development of a catalytic intramolecular cyclopropanation of (R)-1,2-epoxyhex-5-ene gives the key homochiral bicycle[3.1.0]hexan-1-ol, which is then oxidized to the desired ketone. This process has been successfully demonstrated on a multi-kilogram scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…With 1,2-epoxy-5-hexene, it was found that the formation of bicyclic alcohol 9 was a competitive process; indeed changing to Et 2 O as solvent (since such conditions had been found earlier to reduce enamine formation) gave the bicyclic alcohol 9 in 52% yield. Ultimately, this latter observation led to the development of the intramolecular cyclopropanation of unsaturated terminal epoxides . All of the successful enamine-forming reactions that had been carried out thus far had functionality in rather a remote position.…”
Section: Resultsmentioning
confidence: 87%
“…With 1,2-epoxy-5-hexene, it was found that the formation of bicyclic alcohol 9 was a competitive process; indeed changing to Et 2 O as solvent (since such conditions had been found earlier to reduce enamine formation) gave the bicyclic alcohol 9 in 52% yield. Ultimately, this latter observation led to the development of the intramolecular cyclopropanation of unsaturated terminal epoxides . All of the successful enamine-forming reactions that had been carried out thus far had functionality in rather a remote position.…”
Section: Resultsmentioning
confidence: 87%
“…Instead, exo -bicyclo[4.1.0]heptan-2-ol ( 4 ) could be accessed directly in high diastereomeric excess via a ring-opening of epichlorohydrin ( 7 ) by the requisite homoallylic Grignard reagent and cyclisation with lithium 2,2,6,6,-tetramethylpiperidide (LTMP) through conditions initially described by Hodgson and co-workers and later optimised for substrates such as 8 . 25,26…”
Section: Resultsmentioning
confidence: 99%
“…The medicinal chemistry synthesis of ( R )-1 involved 15 steps and nine chromatographic purifications (Scheme ). Chiral bicyclic ketal 4 was prepared from the corresponding ketone reported in the literature and 1,2-diphenylethane-1,2-diol . Stereoselective ring-opening iodination from 4 to 5 was conducted using iodotrimethylsilane (TMSI) according to the published method .…”
Section: Introductionmentioning
confidence: 99%